Effects of seed pre-treatments on the germination of Dioscoreophyllum cumminsii - Bamigboye, Tolulope Olaseini; Kayode, Joshua (International Journal of Biological Research, 2016)
The effect of various seed pre-treatments on the germination of Dioscoreophyllum cumminsii was examined in this study. The pre-treatments included seeds with their testa removed, intact seeds soaked in GA3, seeds soaked in GA3 for one hour after which their gelatinous covers were removed, seeds soaked in GA3 for one hour after which their testa were removed and seeds tied in polythene for 2 days. Intact seeds sown directly without any treatment served as control. Results obtained revealed that while germination did not occurred in seeds whose testa were removed and seeds soaked in GA3 for1 hour after which their testa were removed, germination occurred in other treated seeds and the control. Also while germination occurred in the first 5 weeks in seeds soaked in GA3 and seeds soaked in GA3 for 1 hour after which their gelatinous covers were removed, germination first occurred in 9 days in seeds soaked in GA3 for 1 hour after which their gelatinous covers were removed and in10 days in intact seeds soaked in GA3. Growth occurred in other treated seeds at 11-15weeks experimental time. At 25 weeks experimental time, intact seeds soaked in GA3 had the highest % germination and the germination occurred within the shortest experimental time.